2012
DOI: 10.1124/dmd.112.045187
|View full text |Cite
|
Sign up to set email alerts
|

Key Role of Nuclear Factor-κB in the Cellular Pharmacokinetics of Adriamycin in MCF-7/Adr Cells: The Potential Mechanism for Synergy with 20(S)-Ginsenoside Rh2

Abstract: ABSTRACT:We have previously demonstrated that ginsenoside 20(S)-Rh2 is a potent ATP-binding cassette (ABC) B1 inhibitor and explored the cellular pharmacokinetic mechanisms for its synergistic effect on the cytotoxicity of Adriamycin. The present studies were conducted to elucidate the key factors that influenced ABCB1 expression, which could further alter Adriamycin cellular pharmacokinetics. Meanwhile, the influence of 20 (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 50 publications
0
27
0
Order By: Relevance
“…In order to further elucidate the underlying mechanisms of ROS-induced MDR, immunofluorescence staining was performed to examine several transcriptional factors in close relationship with oxidative stress, including Nrf2, NF- κ B-p65, and HIF-1 α , which were also widely reported as regulators of efflux transporter like P-gp and MRP1 [2124]. Our results showed that Nrf2, NF- κ B-p65, and HIF-1 α were found to be highly expressed in MCF-7/ROS cells compared to control MCF-7 cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to further elucidate the underlying mechanisms of ROS-induced MDR, immunofluorescence staining was performed to examine several transcriptional factors in close relationship with oxidative stress, including Nrf2, NF- κ B-p65, and HIF-1 α , which were also widely reported as regulators of efflux transporter like P-gp and MRP1 [2124]. Our results showed that Nrf2, NF- κ B-p65, and HIF-1 α were found to be highly expressed in MCF-7/ROS cells compared to control MCF-7 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Firstly, overexpressions of functional P-gp and MRP1, which are classic efflux mechanisms of anticancer drugs and correlate broadly with negative treatment response [44], were found in MCF-7 cells after long-term treatment with both H 2 O 2 and GSH. Secondly, the transcriptional factors of efflux transporter, such as Nrf2, NF- κ B, and HIF-1 α [2124], were also upregulated in MCF-7/ROS cells. Importantly, the elevated levels of Nrf2 and HIF-1 α were mainly localized in the nuclei of MCF-7/ROS cells, which suggested them in activation.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the MAPK/NF-κB pathway mediates doxorubicin-induced P-gp expression in MCF-7/ Adr cells and subsequently alters the cellular pharmacokinetics of doxorubicin (3). Paracrine signaling through the receptor activator of the NF-κB (RANK) pathway was reported to promote the development of mammary stem cells and breast cancer, and high levels of RANK were found in human primary breast adenocarcinomas that lack expression of the hormone receptors estrogen and progesterone (triple-negative breast adenocarcinomas) and in tumors with a high pathological grade and proliferation index; in addition, high RANK/RANKL expression was significantly associated with metastatic tumors.…”
Section: Discussionmentioning
confidence: 99%
“…NF-κB is reported to be involved in regulating the expression of MDR1 and CD44 genes in multiple cancer cells (3)(4)(5)(6)(7), and it has been found that the CD44-hyaluronan (HA) interaction induces ankyrin binding to P-gp, resulting in the efflux of chemotherapeutic drugs and development of MDR in cancer (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the exact signaling pathways and targets mediating the antitumor properties of G-Rh2 in lung cancer have yet to be elucidated (Zhang et al, 2012;An et al, 2013;Kim et al, 2014). This study investigates the molecular pathways associated with G-Rh2 that regulate cell proliferation inhibition and apoptosis induction in the human lung cancer cell line A549.…”
Section: Introductionmentioning
confidence: 99%